Overview of the rubberwood industry - Hung T K (Ensuring sustainability and Competitiveness of the NR industry: Proceedings of the Rubber Growers' Conference 1995, Kuala Lumpur, Malaysia, p287-308, 1995)
This paper briefly reviews the current status of the rubberwood industry, the demand and supply and future prospects of further processing of rubberwood. It also attempts to discuss some of the issues related to the future growth of the rubberwood industry. Two decades ago, rubber trees which were cut down after their economic life for latex production were burnt to clear the land for replanting and only an insignificant amount was used as a timber resource. Recognising the potential of rubberwood, the Ministry of Primary Industries has, in 1978, established a Rubberwood Research Committee to co-ordinate research in the utilisation of this timber. The government has through the Malaysian Timber Board(MTIB), actively promoted the usage and export of rubberwood to the world market. As a result of the successful discovery of presrvation, processing and drying techniques by RRIM and FRIM, rubberwood has become an important source of raw material for the wood-based industries. The export of rubberwood sawn timber has increased tremendously over the last decade before it was prohibited. Rubberwood sawn timber exports increased from 17 000 m3 valued at RM4.5 million in 1980 to 221 000 m3 valued at RM98.9 million in 1989. However, following the imposition of an export levy and quota by the government with the objective of encouraging more downstream activities and the production of value-added items, export of rubberwood sawn timber declined. By 1994 only 45 000 m3 worth RM35.9 million were exported. Conversely, as a result of the imposition of this levy and quota, the export value of rubberwood finished products, mainly in the form of furniture components increased from RM12.5 million in 1985 to RM1.1 billion in 1994. The Malaysian rubberwood wood-based industry has achieved rapid growth in the last few years, producing a wide range of furniture products, joinery, panel boards and other finished products. However, future growth will very much depend on the availability of supply and also on Malaysian manufacturers' ability to penetrate new markets and complete successfully in the world market. Owing to the rapid increase in the utilisation of rubberwood sawn timber, the issue of inadequate supply has often been discussed in many dialogues and forums. There is adequate supply of rubberwood logs to cater for future expansion of the rubberwood wood-based industries. The problem appears to be in inadequate milling capacity and logistic difficulties in certain locations. Currently only around 60;of the logs available and suitable for conversion into sawn timber and plywood is being utilised. This under-utilisation of logs available has adversely affected the production of rubberwood sawn timber and plywood. The seasonal element of replanting rubber tree has aggravated the supply availability of rubberwood sawn timber.
Keywords: Rubberwood industry